(untitled) (Plant Tissue Culture and Biotechnology, 2023)
Mimusops laurifolia (Forssk.) Friis is an endangered medicinal plant and natural propagation of this plant through seeds is found to be very difficult due to its hard seed coat. To conquer this problem, an efficient in vitro seed germination as well as subsequent in vitro regeneration technique has been developed in conserving this endangered plant species. Seed germination was achieved on half strength of MS (HMS), full strength MS (FMS) and MS medium supplemented with different concentration and combination of Plant Growth Regulators (PGR) like BA, Kn and GA. The highest seed germination rate (18%) was obtained from water soaking de-coated seeds inoculated on full strength of MS (FMS), on the other hand, 12% germination of seeds was recorded on HMS medium, but both the conditions required more than 90 days to germinate. A similar rate of germination was also found on MS with PGRs, but it required 55-60 days. Best responses towards seed germination with elongated shoots (2.8 cm and 3.0 cm) were obtained when seeds were inoculated on MS with 3.0 mg/l BA, 0.5 mg/l Kn and 0.2 mg/l GA. After a long period of period of 8 months following germination, seedlings produced elongated tap roots only. Rooted seedlings were successfully transferred to soil for their further growth and development. Apart from this, for in vitro regeneration of shoots, explants of nodal segments and shoot tips from the natural plant were cultured on woody plant medium (WPM) supplemented with various combination and concentration of BAP, Kn and TDZ. In these cases, there was no positive response recorded towards the initiation of shoots from nodal segment and shoot tips. Plant Tissue Cult. & Biotech. 33(2): 143-153, 2023 (December)